Connected Futures: Exploring IoT Development in Malaysian SMEs for Industry 4.0 - Amiry Syafy Mohammad Azhar,; Syed Muizzuddin Syed Anuar,; Muhammad Iqbal Darus,; Mohamad Zulfadhli Othman,; Amirul Haziq Zaharuddin,; Muhammad Hilmi Faris Mohd Esa,; Haikal Iskandar,; Muhammad Nazraie Mohd Jawawi,; Nur Liyana Sulaiman,; Mazidah Mat Rejab, (Applied Information Technology And Computer Science, 2023)
This qualitative study explores the current state of Internet of Things (IoT) implementation in Malaysian small- and medium-sized enterprises (SMEs) within the framework of Industry 4.0. Through online interviews and a focus group involving five participants from three SMEs, the research reveals a relatively low adoption of Industry 4.0 in Malaysian manufacturing SMEs. Challenges include the imperative for education and training, budget constraints, and a lack of experience among workers. Despite these hurdles, positive outcomes of IoT implementation emerge, such as enhanced internal communication, error reduction, and improved product quality and safety. The study concludes by presenting an IoT framework, developed collaboratively with experts, offering a strategic tool for Malaysian SMEs navigating the landscape of Industry 4.0 and facilitating advancements in the manufacturing sector.